Assessing the availability of LLINs for continuous distribution through routine antenatal care and the Expanded Programme on Immunizations in sub-Saharan Africa. (December 2016) - Theiss-Nyland, Katherine; Lynch, Michael; Lines, Jo
Abstract Background In addition to mass distribution campaigns, the World Health Organization (WHO) recommends the continuous distribution of long-lasting insecticidal nets (LLINs) to all pregnant women attending antenatal care (ANC) and all infants attending the Expanded Programme on Immunization (EPI) services in countries implementing mosquito nets for malaria control. Countries report LLIN distribution data to the WHO annually. For this analysis, these data were used to assess policy and practice in implementing these recommendations and to compare the numbers of LLINs available through ANC and EPI services with the numbers of women and children attending these services. Methods For each reporting country in sub-Saharan Africa, the presence of a reported policy for LLIN distribution through ANC and EPI was reviewed. Prior to inclusion in the analysis the completeness of data was assessed in terms of the numbers of LLINs distributed through all channels (campaigns, EPI, ANC, other). For each country with adequate data, the numbers of LLINs reportedly distributed by national programmes to ANC was compared to the number of women reportedly attending ANC at least once; the ratio between these two numbers was used as an indicator of LLIN availability at ANC services. The same calculations were repeated for LLINs distributed through EPI to produce the corresponding LLIN availability through this distribution channel. Results Among 48 malaria-endemic countries in Africa, 33 malaria programmes reported adopting policies of ANC-based continuous distribution of LLINs, and 25 reported adopting policies of EPI-based distribution. Over a 3-year period through 2012, distribution through ANC accounted for 9 % of LLINs distributed, and LLINs distributed through EPI accounted for 4 %. The LLIN availability ratios achieved were 55 % through ANC and 34 % through EPI. For 38 country programmes reporting on LLIN distribution, data to calculate LLIN availability through ANC and EPI was available for 17 and 16, respectively. Conclusions These continuous LLIN distribution channels appear to be under-utilized, especially EPI-based distribution. However, quality data from more countries are needed for consistent and reliable programme performance monitoring. A greater focus on routine data collection, monitoring and reporting on LLINs distributed through both ANC and EPI can provide insight into both strengths and weaknesses of continuous distribution, and improve the effectiveness of these delivery channels.